Mediating effect of job stress on the relationship between job demands, job resources and sickness absence a study among nurses in Malaysia - Yu, Chye Wah (2014)
The issue of absenteeism has emerged as one of the main administrative problems in many large as well as small organizations. Sickness absenteeism or involuntary absence also affects the productivity and economic performance of an organization. The main purpose of this study is to examine the predictors of sickness absence and further determine the relationships between job demands, job resources, job stress and sickness absence. About 1,300 hospital nurses of various grades were selected randomly from six regional hospitals located in the northern states of peninsular Malaysia to participate in this study. The study was conducted in two phases. Sick leave data from the employer’s sick leave registry was procured in the first phase of the study for a period of four consecutive months from February to May 2011. The second phase commenced in the mid of the sick leave data collection stage with the administration of survey questionnaires to the targeted participants. Hierarchical multiple regression analysis was used to examine the relationship between job demands, job resources, job stress and sickness absence; The study also investigated the mediating role of job stress on the relationship between job demands, job resources and sickness absence. The results found that workloads, co-worker support and job feedback were significantly related to all dimensions of job stress. Physical demands, job complexity, job feedback, job stress (physical and behavioural stress) were correlated with sickness absence. The findings also revealed the mediating effect of job stress (specifically physical and behavioural stress) on the relationship between job demands (physical demand and job complexity), job resources (job feedback) on sickness absence. Overall this study provided support to the job demands-resources (JD-R) model, and filled the research gaps in the mediating role of job stress. The implications, limitation of the study and future research direction were also discussed in this study.